FUZZY LOGIC FOR DETERMINING THE POTENTIAL OF SOLAR ENERGY POWER PLANT IN SOUTH LIBYA - Zakariya Ali Saeid Saeid; Muhamad Haddin; Arief Marwanto; Muhammad Qomaruddin (Universitas Islam Sultan Agung, 2020)
Energy models also help in integrated assessment considering availability, potential, economics, emission, technology, social acceptance etc Libya is an oil exporting country located in the middle of North Africa, with 6 million inhabitants distributed over an area of 1,750,000 Km2. The problem of this research is the potential of solar energy that is used can be used to overcome the energy needs in South Libya where people are densely populated but need a lot of electrical energy. The potential energy needs of electricity are big because south of Libya many densely populated people need big electricity. Also whether the function of Fuzzy logic is to be able to do the right way to map an input space into an output space based on the concept of fuzzy. The objective of this research is to analyse potential of solar energy generation using fuzzy logic in South Libya. The authenticity of this research is using fuzzy logic in South Libya to overcome the problem that is the demand of huge electricity from solar energy generation. This research is quantitative research with simulation or experimental research to make verification with MATLAB simulation (Fuzzy logic approach). In his research will cover in 7 days’ simulation with Matlab, with Fuzzy logic approach, the target is to make simulation panel solar system in South Libya. The determination of potential solar energy power plant in South Libya using fuzzy logic can be seen in the simulation Matlab that proven the Fuzzy Logic approach have achieved the optimal solar energy power plant. The result showed that in Libya the consumption is 10020 MW with 3.504.000 homes and 2860 W, so need 67 solar panels. The low is when the humidity between 40%-60% (0.6 kW), Medium when the humidity 60%-80% (2.86kW) and High when humidity 80%-100% (3.9 kW).